Synthesis of deep-cavity fluorous calix[4]arenes as molecular recognition scaffolds - Osipov, Maksim (Beilstein-Institut, 2008)
Several lower-rim perfluoroalkylated (fluorous) calix[4]arenes have been synthesized by O-alkylation of the parent calix[4]arene. The compounds are formed in the cone conformation. They are soluble in several fluorous solvents and show promise for use in sensing, selective extractions and other applications.